2018
DOI: 10.2478/raon-2018-0014
|View full text |Cite
|
Sign up to set email alerts
|

In silico selection approach to develop DNA aptamers for a stem-like cell subpopulation of non-small lung cancer adenocarcinoma cell line A549

Abstract: BackgroundDetection of circulating lung cancer cells with cancer-stem like characteristics would represent an improved tool for disease prognosis. However, current antibodies based methods have some disadvantages and therefore cell SELEX (Systematic Evolution of Ligands by Exponential Enrichment) was used to develop DNA aptamers, recognizing cell surface markers of non-small lung carcinoma (NSLC) cells.Materials and methodsThe human adenocarcinoma cell line A549 was used for selection in seven cell SELEX cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Therefore, Apta 99 is the candidate aptamer with the greatest thermodynamic stability. Among the Cell-SELEX studies present in the literature, it is observed that the total ΔG values of aptamers are variable within a group of negative values [25,26].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, Apta 99 is the candidate aptamer with the greatest thermodynamic stability. Among the Cell-SELEX studies present in the literature, it is observed that the total ΔG values of aptamers are variable within a group of negative values [25,26].…”
Section: Resultsmentioning
confidence: 99%
“…This was exploited to bind DNA oligomers that were conjugated to BG to SNAP-decorated dendrimersomes. An ALC aptamer (EJ4), a DNA therapeutic that has been used for study and treatment of lung carcinomas, was selected for this experiment (50, 51). This 40+ nucleotide ssDNA molecule was also conjugated to a fluorescein amidite (FAM) dye to enable visualization by confocal fluorescence microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…A variant of this selection has been then developed by Vidic et al [ 15 ] with the final aim to select aptamers against NSCLC circulating tumor cells with the ability to also recognize cancer-stem like cells. The authors used A549 cells as positive target and human blood cells as negative control.…”
Section: Selex Technologies To Generate Nsclc Targeting Aptamersmentioning
confidence: 99%
“…More recently, the same authors used two DNA aptamers (ECM-APT-01 and ECM-APT-02) directed against EpCAM to isolate and detect EpCAM + CTCs in clinical blood samples with a detection limit of 0–2 cells/mL of blood [ 20 ]. Further, Vidic and colleagues demonstrated that an aptamer (A155_18) isolated by cell-SELEX (see previous section for details) showed a good potential as a diagnostic tool for the detection of NSCLC CTCs expressing the stem cell marker CD90 [ 15 ].…”
Section: Nucleic Acid Aptamers For Nsclc Detectionmentioning
confidence: 99%